Brain levels of high‐energy phosphate metabolites and executive function in geriatric depression. (18th February 2016) - Harper, David G.; Joe, Elizabeth B.; Jensen, J.Eric; Ravichandran, Caitlin; Forester, Brent P.
Abstract : Objectives: Depression in late life has been associated with difficulties in cognitive processing, particularly in the domains of executive function, processing speed and memory, and increases the risk of developing dementia suggesting a neurodegenerative phenotype. Mitochondrial dysfunction is frequently an early event in neurodegenerative illnesses and may be operative in patients with late life depression. Phosphorus magnetic resonance spectroscopy (31P MRS) allows for the quantification of bioenergetic molecules produced by mitochondria. Methods: Ten patients with late life depression and eight normal elderly controls were studied with Stroop color and interference tests, which are widely used measures of processing speed and executive function, respectively, followed by (31P) MRS 3‐dimensional chemical‐shift imaging measuring levels of adenosine triphosphate, phosphocreatine, inorganic phosphate, and pH over the whole brain. Results: In all subjects, gray matter phosphocreatine was positively associated with Stroop interference. Levels of white matter adenosine triphosphate were associated with Stroop interference in subjects with late life depression but not normal elderly. There was also a complementary association between white matter inorganic phosphate and Stroop interference in late life depression patients. Conclusions: These findings suggest two independent sources of executive function dependence on bioenergetic state in the aging brain. The dependence of executive function performance in subjects with late life depression on ATP in white matter may be associated with mitochondrial impairment and is consistent with predictions of the vascular depression hypothesis. Further research with wider neuropsychological testing targeting bioenergetic markers could help clarify the scope of these effects. Copyright © 2016 John Wiley & Sons, Ltd